2002
DOI: 10.1046/j.1471-8286.2002.00297.x
|View full text |Cite
|
Sign up to set email alerts
|

Transferability of microsatellite markers from Eucalyptus spp. to Eugenia dysenterica (Myrtaceae family)

Abstract: Cagaita (Eugenia dysenterica) is a widespread plant found in the Brazilian cerrado. Its fruit is used for popular consumption and for industrial purposes. A battery of 346 primer pairs developed for Eucalyptus spp. was tested on cagaita. Only 10 primer pairs were found to be transferable between the two species. Using a polyacrilamide gel, an average of 10.4 alleles per locus was detected, in a sample of 116 individuals from 10 natural populations of cagaita. Seven polymorphic loci allowed estimation of geneti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
26
0
5

Year Published

2003
2003
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(35 citation statements)
references
References 10 publications
4
26
0
5
Order By: Relevance
“…The 356 primers tested were classified according to the quality obtained in the PCR: 2.8% (ten pairs of primers) amplified clear SSR products, 30.0% presented non specific band amplification and 67.2% did not amplify any band (Zucchi et al 2002).…”
Section: Transferability Of Ssr Eucalyptus Primers To Eugenia Dysentementioning
confidence: 99%
“…The 356 primers tested were classified according to the quality obtained in the PCR: 2.8% (ten pairs of primers) amplified clear SSR products, 30.0% presented non specific band amplification and 67.2% did not amplify any band (Zucchi et al 2002).…”
Section: Transferability Of Ssr Eucalyptus Primers To Eugenia Dysentementioning
confidence: 99%
“…We observed loci with 3 (mAoR7 and mAoR48) to 8 (mAoR11) alleles. The average number of alleles per locus was less than those found for Eugenia dysenterica (10.4) (Zucchi et al, 2002) and Festuca arundinacea (7.8) (Elazreg et al, 2011). The observed number of alleles per locus was closer to the values observed for Hymenaea stigonocarpa (6.43) (Ciampi et al, 2008), Dactylis glomerata (5.45), Lolium perenne (4.50) (Litrico et al, 2009) and Blighia sapida (3.7) (Ekué et al, 2009).…”
Section: Characterization Of the Polymorphic Ssr Locimentioning
confidence: 41%
“…Several studies have shown that the homology of DNA sequences in microsatellite flanking-region pairs has allowed SSR markers that have been developed for one species to be transferred to another species of the same genus or even different genera (Zucchi et al, 2002;Ciampi et al, 2008;Ekué et al, 2009;Feres et al, 2009;Litrico et al, 2009;Elazreg et al, Use of SSR markers from A. occidentale to A. humile 2011; Cristofani-Yaly et al, 2011). The success of marker transfer is inversely proportional to the evolutionary distance between the 2 species (Schlotterer et al, 1991;Moore et al, 1991;FitzSimmons et al, 1995;Rossetto, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Em geral, a amplificação de locos com repetições tetranucleotídicas é de interpretação mais fácil (PINTO et al, 2001). Entretanto a conservação das regiões flanqueadoras dos microssatélites possibilita a utilização de iniciadores específicos em outras espécies pertencentes a um mesmo gênero ou entre gêneros de uma mesma família (FERREIRA;GRATTAPAGLIA, 1998, ZUCCHI et al, 2002. A necessidade de uma proximidade filogenética é um fator que garante o êxito na transferência de primers, no entanto ela pode ser afetada por fatores como o tamanho e complexidade do genoma em questão e se os microssatélites pertencem a regiões codificantes .…”
Section: Marcadores Microssatélitesunclassified
“…Essa característica permitiu a realização de inúmeros estudos, dentre os quais pode-se destacar os trabalhos com espécies do Cerrado: Zucchi et al (2002) de Eucalyptus spp para Eugenia dysenterica; Martins et al (2006) de Capsicum spp para Solanum lycocarpum e Ciampi et al (2008) de Hymenaea courbaril para Hymenaea stigonocarpa, entre outros.…”
Section: Marcadores Microssatélitesunclassified